1975
DOI: 10.1084/jem.142.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Binding properties of immunoglobulin combining sites specific for terminal or nonterminal antigenic determinants in dextran.

Abstract: Binding constants of the dextran-reactive BALB/c mouse IgA myeloma proteins W3129 and QUPC 52 have been determined for each member of the isomaltose series of oligosaccharides and for methyl alphaDglucoside. Protein W3129 has maximum complementarity for isomaltopentaose (IM5) deltaf degrees = 7,180 cal/mol) with 55-60% of the total binding energy directed against methylalphaDglucoside. Protein QUPC 52 gives maximum binding with isomaltohexaose (IM6) (deltaF degrees = -5,340 cal/mol) and has about 70% of its to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 68 publications
6
64
0
Order By: Relevance
“…Whereas these findings suggest that the OL-4 structure makes a major contribution to antigenicity, the location of the respective determinant within the polysaccharide is not known. Since the CIP is linear, antibodies that are inhibited by OL-4 may react with repeating nonterminal antigenic determinants, as has been found with antibodies that precipitate linear chains of al-6-linked dextran (11). However, CIP molecules with multiple nonreducing ends would occur if branching were present or if linear chains were cross-linked by cell wall peptidoglycan.…”
Section: Discussionmentioning
confidence: 88%
“…Whereas these findings suggest that the OL-4 structure makes a major contribution to antigenicity, the location of the respective determinant within the polysaccharide is not known. Since the CIP is linear, antibodies that are inhibited by OL-4 may react with repeating nonterminal antigenic determinants, as has been found with antibodies that precipitate linear chains of al-6-linked dextran (11). However, CIP molecules with multiple nonreducing ends would occur if branching were present or if linear chains were cross-linked by cell wall peptidoglycan.…”
Section: Discussionmentioning
confidence: 88%
“…Early work on anti-polysaccharide antibodies suggested that carbohydrate epitopes could vary from one to approximately seven residues, the upper limit being determined by the surface available at the antigen-binding site (16). It was concluded that small epitopes generally include the nonreducing terminal residue, whereas larger epitopes are located along the length of the polysaccharide chain (17). It was further suggested that small epitopes bind to cavity-type antigen-binding-site topologies, whereas larger internal epitopes are recognized by groove-type topologies (18).…”
Section: Discussionmentioning
confidence: 99%
“…This cross-reactivity between GBM and GCM is not an unexpected effect, because several references describe the superior immunogenicity of the terminal nonreducing end of polysaccharides and the similar region of polypeptides (51)(52)(53)(54).…”
Section: Cross-reactivity Between Gbm and Gcm Cpmentioning
confidence: 88%